Indonesian National Narcotics Agency’s Role in Implementing UNODC’s Alternative Development in 2019-2022 - Guritno, Wulan Suci; Hidayatullah, Nur Luthfi (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This research focuses on the role of the Indonesian National Narcotics Agency (BNN) in implementing the United Nations Office on Drugs and Crimes’ (UNODC) Alternative Development program in 2019-2022. This study uses descriptive qualitative method and the alternative development concept to examine the study case. Data collection technique includes documentation from literature sources and interviews. The results of this research found that the Indonesian National Narcotics Agency has implemented the UNODC’s Alternative Development in 2019-2022 by creating a Grand Design of Alternative Development (GDAD) in Aceh Province, as a pilot project. The GDAD in Aceh diverts farmers’ narcotic plantation into alternative agricultural commodities. Hence, the BNN has implemented all of the UNODC’s Alternative Development components, including Agricultural Development, Basic Infrastructure, Community Development, Education, Environmental Protection, Gender Equality, Health, Improved Markets, and Security Rule of Law. The program was considered effective, because many farmers in Aceh whom had previously planted narcotic plants converted their farmland into plantation of crops with high selling values.